2021
DOI: 10.1007/s00221-021-06043-6
|View full text |Cite
|
Sign up to set email alerts
|

Whole-hand perceptual maps of joint location

Abstract: Hands play a fundamental role in everyday behaviour. Nevertheless, healthy adults show striking misrepresentations of their hands which have been documented by a wide range of studies addressing various aspects of body representation. For example, when asked to indicate the location within the hand of the knuckles, people place them substantially farther forward than they actually are. Previous research, however, has focused exclusively on the knuckles at the base of each finger, not considering the other knuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
1
1
0
Order By: Relevance
“…A subsequent study using the same methodology also reported participants overestimated the width of the torso, although participants also overestimated torso length, which differs from the current study ( Fuentes et al, 2013a ). For height, if considering the trunk overall with thorax-to-hips height, participants tended to underestimate their trunk in the vertical axis, consistent with previous findings of underestimation in length or proximo-distal direction, for the hand ( Cocchini et al, 2018 ; Longo, 2017b , 2018 ; Longo & Haggard, 2010 , 2012a , 2012b ; Longo & Holmes, 2020 ; Longo et al, 2015b ; Mattioni & Longo, 2014 ; Myga et al, 2021 ; Peviani & Bottini, 2020 ; Saulton et al, 2015 , 2016 , 2017 ; Tamè et al, 2017 ), face ( Fuentes et al, 2013c ) and leg ( Stone et al, 2018 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A subsequent study using the same methodology also reported participants overestimated the width of the torso, although participants also overestimated torso length, which differs from the current study ( Fuentes et al, 2013a ). For height, if considering the trunk overall with thorax-to-hips height, participants tended to underestimate their trunk in the vertical axis, consistent with previous findings of underestimation in length or proximo-distal direction, for the hand ( Cocchini et al, 2018 ; Longo, 2017b , 2018 ; Longo & Haggard, 2010 , 2012a , 2012b ; Longo & Holmes, 2020 ; Longo et al, 2015b ; Mattioni & Longo, 2014 ; Myga et al, 2021 ; Peviani & Bottini, 2020 ; Saulton et al, 2015 , 2016 , 2017 ; Tamè et al, 2017 ), face ( Fuentes et al, 2013c ) and leg ( Stone et al, 2018 ).…”
Section: Discussionsupporting
confidence: 85%
“…Investigators have attempted to map the body model by asking participants to localise the position of body landmarks without the use of visual information. These studies have all yielded results showing systematic distortions of the body model at the hand ( Ambroziak et al, 2018 ; Cocchini et al, 2018 ; Longo, 2015b , 2017b , 2018 ; Longo & Haggard, 2010 , 2012a , 2012b ; Longo & Holmes, 2020 ; Longo et al, 2015b ; Margolis & Longo, 2015 ; Mattioni & Longo, 2014 ; Myga et al, 2021 ; Peviani & Bottini, 2020 ; Saulton et al, 2015 , 2016 , 2017 ; Tamè et al, 2017 ), the forearm ( Longo, 2017b ), face ( Fuentes et al, 2013c ; Longo & Holmes, 2020 ; Mora et al, 2018 ) and leg ( Stone et al, 2018 ).…”
mentioning
confidence: 99%